Vacant city : Brussels' Mont des Arts Reconsidered. - Avermaete, Tom, 1971-; Borret, Kristiaan; Braeken, Jo; Brams, Koen; Carrilho da Graça, João Luis; Cohen, Maurizio; David, Catherine; De Clercq, Dieter; De Meulder, Bruno; De Meyer, Ronny; De Schaepdrijver, Sophie C.; Graw, Isabelle; et al. (Rotterdam : NAI Uitgevers, 2000)
Vacant City shuttles between the issue of vacant structures in today's cities, the role of culture in urban planning, and the changing significance of the museum. It also inaugurates an innovative planning process which submits to the cultural event Brussels 2000, European City of Culture, a research programme on city development models. It offers a fascinating insight into the particular problems and history of Brussels' Mont des Arts as urban site. The research methods used in the project are urban analysis and urban history, architectured theory and cultural philosophy, but above all design and programming. Internationally renowned architects like Atelier Seraji, João Luis Carrilho Da Graça, Design + Urbanism, Max. 1 & Crimson, and Riken Yamamoto & Field Shop, and cultural critics and philosophers such as Catherine David, Isabelle Graw, Hilton Judin and Bart Verschaffel produced at the behest of Brussels 2000 spatial as well as development concepts for the Mont des Arts, which are extensively documented and analysed in this publication.
Engels
De Kunstberg... stad op de helling : Laboratorium voor de stad van morgen, Brussel 2000, 25.10 -17.12.2000
boek
Keywords: Horta, Victor; Judin, Hilton; Carrilho da Graça, João Luis; Yamamoto, Riken; Field Shop; Max. 1 Crimson; Atelier Seraji; Brussel